FINANCIAL DISTRESS DAN MANAJEMEN LABA TERHADAP KECURANGAN LAPORAN KEUANGAN (Studi Pada Perusahaan BUMN Kelompok Danantara Periode 2022-2024) - Seftiana, Rahma; Singagerda, Faurani I Santi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2026)
This study aims to examine the effects of financial distress, proxied by the Z-Score, and earnings management, proxied by discretionary accruals, on financial statement fraud, proxied by the F-Score, in Danantara-group state-owned enterprises listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The study uses secondary data obtained from annual financial reports on the IDX official website and company annual reports. A purposive sample of 11 companies produced 33 observations. Analysis was conducted using panel data regression with a Fixed Effects Model in E-Views 10, and the data met classical assumption tests (multicollinearity and heteroskedasticity). The results indicate that financial distress has a positive and significant effect on financial statement fraud, while earnings management does not have a significant effect on financial statement fraud. The model shows a high Adjusted R-squared, explaining a substantial portion of the variation in fraud. These findings reinforce agency theory that financial distress motivates managers toward extreme fraud, whereas earnings management does not substitute for fraud. Practical implications include strengthening internal oversight within Danantara SOEs, proactive management of distress risk, and enhanced reporting transparency to prevent stakeholder losses from fraud. Keywords — financial distress, earnings management, financial statement fraud, SOEs, Danantara